Microstructural and Mechanical Stability of a Ti-50.8 at.% Ni Shape Memory Alloy Achieved by Thermal Cycling with a Large Number of Cycles - Anna Churakova; Dmitry Gunderov (Metals, 2020)
The influence of thermal cycling (TC) with a large number of cycles on the microstructure, the parameters of martensitic transformations (MTs), and the mechanical properties of a Ti-50.8 at.% Ni shape-memory alloy in coarse-grained (CG) and ultrafine-grained (UFG) states was investigated. The effect of microstructural and mechanical stability was found in both coarse-grained and ultrafine-grained states starting from the 100th cycle of martensitic transformations. In addition, an unusual temperature change was observed in martensitic transformations occurring with the formation of an intermediate R phase.